2022
DOI: 10.1007/s12144-022-03444-w
|View full text |Cite
|
Sign up to set email alerts
|

How different online self-presentations relate to life satisfaction differently in college students: The role of positive online feedback and self-esteem

Abstract: In the Internet age, some online factors, such as online self-presentation, related to life satisfaction have received much attention. However, it is unclear whether and how different strategies of online self-presentation are linked to an individual’s life satisfaction differently. Accordingly, the present study examined the possible different relationships between different online self-presentations and life satisfaction with a sample of 460 Chinese college students. Using a series of questionnaires, a moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 109 publications
0
9
0
Order By: Relevance
“…As a key indicator of well-being, life satisfaction refers to how an individual evaluates his or her life during the majority of the time, or for a certain period of time [ 16 , 18 , 38 ]. Numerous personal, psychological, behavioral, interpersonal, and social consequences have been demonstrated to be favorably correlated with it.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…As a key indicator of well-being, life satisfaction refers to how an individual evaluates his or her life during the majority of the time, or for a certain period of time [ 16 , 18 , 38 ]. Numerous personal, psychological, behavioral, interpersonal, and social consequences have been demonstrated to be favorably correlated with it.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In terms of the linkage between life satisfaction and self-presentation, psychological state has been consistently discovered to be positively related to an individual’s self-presentation [ 17 , 18 , 30 ]. For instance, Grieve and Watkinson demonstrated that inauthentic self-presentation on mobile services can be related to numerous psychological problems of maladjustment [ 17 ].…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Social feedback could also provide adolescents with emotional support and informational support, and it is a necessary condition for building strong social ties [ 22 ]. Research also found a mediating role of positive feedback in SNS use and psychological outcomes [ 23 , 24 ]. For example, Liu and Brown found positive feedback mediated the relationship between self-disclosure on SNSs and bonding social capital among Chinese college students [ 22 ].…”
Section: Introductionmentioning
confidence: 99%